(untitled) (Archives of Criminology, 1984)
The study described in the paper and has been conceived as a continuation and partly a repetition or studies carried out in 1961 and 1962 by A. Swięcicki and then in 1968 by J. K. Falewicz. All of these studies were carried out by the Centre for Public Opinion Survey (now: Centre for Public Opinion Survey and Program Studies) of the Committee for Radio and TV in Warsaw. The instrument used in them was a questionnaire filled in by the interviewer during his interview with the respondent. The first study, conducted in February and March 1961, included a sample of a population aged 20 and over, while in the second one, which was made in October 1962, u sample aged 18 and over was included. In both studies, the assumed samples numbered 3000 respondents each, the obtained sample being 95.6 per cent and 93.6 per cent of the assumed sample respectively. The third study was carried out in March and April 1968: it included a sample of population aged 18 and over (assumed sample - 3212 respondents, obtained sample – 91.7 per cent). The present, i.e., the fourth study, was conducted in September 1980 and it included a sample of population aged 16 and over, of the assumed size of 2000 respondents; the obtained sample numbered 1972 persons, which is 98.6 per cent of the assumed one. In the case of all the four studies the deviation of the obtained sample from the assumed one was slight which permitted them to be treated as random sample of the general population. The chief aim of the 1980 study was to obtain data which would be comparable with those previously acquired and those up-to-date, concerning the distribution of consumption of alcohol among the population of Poland. The previous studies, dating back at least a dozen years, were not only old, but they were carried out in the period when general level of consumption of alcohol was approximately half of that in 1980. It seemed more difficult to answer the question to what degree the observations then made still applied to the new situation. There was a demand for some new data it last to replace the guesses made from the factual basis which, as the years went by, became more and more uncertain. In spite of the fact that the present study wbs made in the same way as the previous ones, it seems that the above aims have not been achieved. The data now obtained are not fully comparable with the previous, first of all because the 1980 survey successfully covered a considerably smaller amount of alcohol consumed in our country than those of 1961 and 1962. Undoubtedly, this was caused by various factors, the most important of which being probably the fact that the representation among the respondents of persons who drank intensively and most intensively was scantier in the present study than it had been in the studies conducted by A. Swięcicki. Consequently, the 1961-1962 and 1980 surveys concerned different categories of drinking persons, the ranges of which were not identical in both cases. As regards the scond aim of the study, which was to obtain current data on consumption of alcohol in Poland, we were unsuccessful again, as life proved to run too fast. The 1980 survey was carried out in October 1980, that is one might say at the last moment before the difficulties with alcohol supplies began, as yet unknown in our country, which resulted in regulated sale of alcoholic beverages. This caused the appearance of new phenomena as well as the aggravation of those hitherto existing, Undoubtedly, it was a new phenomenon that people started to buy alcohol not only to consume it, but also to gret rid of the rapidly devaluating money, or in order to obtain a kind of exchange value. Other new phenomena were: trade in coupons entitling one to buy alcohol, and the appearance of black-market prices of spirits produced by the State-controlled distilleries; in certain periods, these prices were twice as high as the official ones. Speaking of aggravation of the existing phenomena, we had in mind first of all the illicit distillation of liquor, the attractiveness of which increased greatly in the face of joint effect of two circumstances: the rapid increase in the price of legally distilled and imported alcohol, and the difficulties in its legal (and even illegal) purchase. It was impossible for the 1980 survey to answer the following questions: what the influence of all these phenomena on the patterns of drinking that had already been shaped before in our country was, and how these patterns were modified. It is known that people drink somewhat differently now. It may be supposed that the persons who used to consume small amounts of alcohol before and who used to drink with restraint now drink less or do not drink at all, while those who used to drink much before - even if they do drink less now, the difference is slight, the illegally distilled liquor playing a greater part in the total amount of alcohol they consume. As to this last problem, opinions are expressed according to which consumption of the illegally distilles liquor has become a much more popular experiences in the course of the ‘80s than it had been before. Finally, conjectures are made that alcohol-dependent persons, after the first period of difficulties with providing themselves with the amount of alcohol which would be adequate to their habits, in general have now found ways to satisfy their needs in this respect. It remains a guess if the above conjectures are true or not, and the same applies to suppositions concerning persistent or temporary character of the abovementioned changes in patterns of consumption of alcohol. Thus the results of the survey describe the situation as it was a few years ago as this situation undoubtedly changed later on. As the paper clearly shows, consumption of alcohol in Poland is a common phenomenon: an everyday habit for many of our fellow citizens, a regular one (though not necessarily at regular intervals)- for the majority. In a statistical-descriptive sense drinking should, therefore, be termed normal behaviour, as it appears more or less regularly in the behaviour of a majority of adult members of our society, whenever they find themselves in situations such as celebrations family, meeting friends, or official occasions. The above remarks by no means solve the question of estimation of drinking, which- in spite of its habitual character in the statistical-descriptive sense- may in some cases be recognized as most deeply pathological in the medical sense, and in the same adn frequently also in other cases- as pathological in its social expression. As regards the medical appraisal- the questionnaire did not contain a large set of questions of this kind, therefore, it was able to yield but a most scanty basis fof conjectures as to the symptoms of alcohol dependence of some of the respondents. The situation was different as regards the social appraisal of the consumption of alcohol. In order to make use of such an appraisal, an initial poblem had to be solved: what amount, frequency, and way of consuming alcohol should or should not be regarded as that included within the limits of a „social norm”. The problem is complex, for, on the one hand, the opinions as to where the limits are vary in our socjety, and, on the other hand, there are probably many such limits, depending not only on the person who is to fix them, but also on that to whom they may apply. It is generally known that in our society there are advocates of prohibition (who are of opinion that zero consumption should be the social norm), as well as propagators of „reasonable consumption” which is a term with many shades, and finally adherents of opinion that consumption of alcohol is a private matter for everyone to decide by himself (that is those who consider any kind of drinking, as well as abstinence, to come within the limits of socially approved norm). Apart from the advocates of the two extreme opinions, which provide one norm for all members of the society, others, i.e., the propagators of „reasonable” drinking tend to emploi a norm according to who the drinking person is. This finds expression in a different attitude towards drinking by men and women, tolerance towards the drinking by adults accompanied by strict disapproval in the case of the youth, different expectations as to the attitude towards alcohol drinking by members of different socio-professional groups. In this situation, with the lack of a common opinion as regards „socially normal” drinking, it seemed preferable to refrain from estimating the alcohol consumption in terms of social pathology. In a survey of alcohol consumption in which samples of population of the entire country or a smaller territory are included, it is vital how the questions about the respondents’ drinking habits are asked. In the research practice, two solutions of this problem have been provided: first, to ask about the last occasion on which the respondent drank, what he drank then, how much he drank and in what circumstances, and second, to ask about his drinking within a given, shorter or longer, period of time. It has been a tradition of Polish studies in this field to choose the first of these solutions, so this method has also been employed in the present study. The last occasion was treated as typical of the respondent’s way of drinking, and a yearly consumption was calculated for each of tchem, as well as for all persons included in the sample. As compared with the data on alcohol sale gathered in our country, it appeared that the 1980 survey covered 43 per cent of the total of consumed vodka. This percentage corresponds to that which can be found in analogous foreign studies, yeti t is considerably lower than the one obtained by A. Święcicki in his 1961 and particularly 1962 studies. The probable effect on the comparability of this studies with the present one has already been discussed above. Interest was also paid in the questionnaire to the consumption of home-made wine, which appeared to account for 39 per cent of the consumption of purchased wine covered by the study, and the consumption of „home-distilled vodka” (i.e., moonshine alcohol) which, according to the present study, accounted for 5.5 per cent of the consumption of purchased vodka. Ona may guess that the latter percentage was in reality higher, and that it has now increased even more. As is generally known, Poland is one of the countries where the general level of consumption of alcohol is medium, yet the structure of consumption is most unfavourable. Over 3/4 of the consumed alcohol is being drunk in Poland in the from of vodka and other strong drinks. A similar structure of consumption can be found in most parts of the Soviet Union, and to a smaller degree in the Scandinavian countries (except Denmark, where the dominating alcoholic beverage is beer). One of the common features of alcohol consumption is its great concentration, which means that relatively few consumers drink a share of alcohol disproportionately large to their number. As revealed by the 1980 survey, 45 per cent of the entire purchased and home-made wine covered by the study was being drunk by3.5 per cent of consumers of wine, 52 per cent of vodka was being drunk by 9 per cent of consumers of vodka, and 46 per cent of beer was being drunk by 10 per cent of consumers of beer. Taking into account that the study included a relatively small numer of persons who drink intensively and particularly those who drink most intensively, the real concentration of consumption of separate types of alcoholic beverages must be expected to be still higher in our country. The interdependence of consumption of different alcoholic beverages is closely connected with the problem of concetration of consumption. It appeared that the fact of drinking one kind of alcoholic beverage augmented the likelihood of drinking another one as well. This convergence was most marked as regards consumption of vodka and beer, as well as vodka and purchased wine (and also purchased and home-made wine); it was the least marked in the case of the consumption of home-made wine and vodka, and home-made wine and beer.Among the persons who drank at least two of the above mentioned kinds of beverages, the frequent drinking of one of them was not necessarily connected with frequent drinking of the other: on the other hand, those who drnak large amounts of one of the beverages, drank also large amounts of the other, while those who drank small amounts of one kind, drank also small amounts of the other. According to the results of our survey, teetotallers, i.e., persons who do not drink alcohol at all, constituted nearly 17 per cent of our respondents. As regards separate kinds of beverages, there were many more persons who did not drink them; yet a significant regularity appeared, which should be stressed in connection with the unfavourable structure of alcohol consumption in our country: the group of persons who never drank vodka was the least numerous, 25 per cent only, while there were 57-58 per cent of persons who never drank purchased wine and beer, and as many as 70 per cent of those who never drank home-made wine (the percentage for moonshine alcohol was 89 per cent). To repeat, not only as much as 71 per cent of alcohol was consumed in our country in the form of vodka (strong drinks) in 1980, but also it was consumed by 75 per cent of the country’s population aged 16 and over. Opportunity, place, and company are the usually distinguished elements of the patterns of alcohol consumption which can be found in the society. The 1980 survey permitted to separate three such patterns (of drinking vodka or wine): family-celebration, friendly-social, drinking for purpose. According to the first one, which has been mentioned by nearly half of the respondents who drank, the opportunity for drinking was a family meeting or celebration, with many participants, the place was a private appartment, the amounts of alcohol consumed were relatively smaller, and the participants were first of all persons who drank less than the average. According to the second pattern, which was mentioned by nearly every third respondent, the opportunity was a social meeting or celebration, in which a smaller number of persons participated (as compared with the family meetings), the place was often also a private appartment, but in every fourth case a restaurant as well, more alcohol was consumed, and among the participants the persons prevailed who drank a little more than the average. According to the third pattern, drinking for purpose, mentioned by every seventh respondent, "no special occasion" was required for drinking, or drinking took place "in order to handle some business which made it necessary to drink a glass", a small group of 3-4 persons participated, the most frequently chosen place, apart from one’s own apartment, was a restaurant or place of employment, a relatively largest amount of alcohol was consumed, and a majority of participants drank much more than the average. As is generally known, a particular problem in Poland is drinking at the place of employment; the Goverment has repeatedly prohibited it, only to learn that the renewal of the prohibition is apparently as timely as it is ineffective. Among the respondents employed in the State-controlled economy, two of every three persons happened to drink at work, every fourth happened to drink at least during the last month. The opportunity was usually a birthday or a name-day; yet every sixth respondent happened to drink at work last "without special reason". The information concerning the frequency of drinking and the amount of alcohol consumed permits one to separate four ways of drinking: much and often, much and seldom, little and often, little and seldom. Among the consumers of different beverages the group of persons drinking little and seldom was the most numerous, particularly as regards the consumers of wine (both purchased and home-made), to a smaller degree - the consumers of vodka (and moonshine alcohol), and to the smallest degree - the consumers of beer. Also the groups of persons drinking much and seldom were relatively numerous, apart from consumers of beer, among whom the second most numerous group was that of persons drinking little and often. Every fourth or fifth consumer of beer, every seventh consumer of vodka, every fifteenth consumer of purchased wine and every twenty-seventh consumer of home-made wine drank much and often. As regards persons who, drank any two of the above mentioned beverages, a convergence of their drinking patterns could be noticed which consisted in the following regularity: if one of the beverages was consumed according to one of the patterns, the other was generally also consumed according to the same pattern. Drinking "too much", "several consecutive days", „more often than the respondent wishes”, were considered an indicators of alcohol abuse. The persons who never happened to drink like this drank, on the whole, considerably smaller amounts of vodka than the average; those who had happened to drink like this before consumed markedly more vodka than the average; while those who have happened to drink like this at the time of the study consumed over twice as much vodka than the average. As shown by the analysis of answers to a variety of questions in the questionnaire, the amount of consumed alcohol is connected with the respondent’s satisfaction with his life and his relations with others. Thus persons who were of opinion that life generally brings the people more good than evil used to drink significantly less (vodka, purchased wine, as well as beer) than those who thought the opposite. Likewise, the respondents who considered themselves frequently underestimated by their closest family, drank significantly more than those who thought that they happened, though seldom, to have been underestimated. Finally, the persons who were of the opinion that their relations with their families, neighbours, workmates, and superiors went badly, used to drink significantly more than those who had no problems in this field. The drinking persons’ experiences with alcohol are both good and bad, and the tendency to study first of all, if not exclusively, the latter does not seem appropriate. In the 1980 survey questions about both kinds of experience were asked, which brought in a good deal of interesting information. Thus it appeared that the drinking of a certain amount of alcohol in the company of a given person helped to solve professional prbblems for a number of persons which was two and a half times larger than the number of those whose drinking brought about serious professional trouble. In over 2/5 of the persons examined, alcohol helped to improve their relations with close friends and relatives, while it helped every third of them to settle their own subsistence problems profitably. As for the troubles resulting from drinking, it is striking that persons problems (poor health, family or financial problems) were mentioned two or three Times more often than those connected with the respondents’ participation in a broader social environment (problems with neighbours, professional problems, and those with the authorities). The above seems to prove that in the customs and climate which exists in our country, the drinking persons perceive alcohol as bringing them more good than evil. As revealed by a closer analysis of the good and bad experience involved in drinking, they usually coexisted: the more good experience the respondents had, the larger was also the amount of their bad experience, and the more they drank. One could say that the persons who used to drink much and thus fell into trouble realized at the same time that drinking brought them various forms of satisfaction and profits. This undoubtedly intensified their tendency do drink, in spite of the trouble resulting from drinking. The last problem to be discussed in the paper is the respondents’ victimization by aggressive behaviour of drunken persons and by their own intoxication. As regards the first problem, it should be stressed that contacts with attempted physical aggression (a drunken person trying to stop or catch the respondent) were frequent: within the year previous to the study nearly every third respondent experienced such an event. Every ninth respondent fell victim to more serious acts of aggression ("more serious" meaning at least being physically assaulted). As regards unpleasant consequences of the respondent being intoxicated, the most frequent of them were: getting involved in a quarrel (which happened to every fourth or fifth respondent within the year previous to the study), loosing money or other valuable things (which happened to every ninth respondent). It is significant that the persons who experienced unpleasant consequences of being in the state of intoxication, drank over twice as much as on the average. The results of the study the extent, structure, and some correlates of the consumption of alcohol in our country described in the paper are an attempt at filling the gap in the studies of this problem which emerged in the ’70s. Such studies should be repeated at not too, long intervals, in order to prevent the occurence of such gaps in the future